'Energizing' Relations: Western European industrialists and China's dream of self-reliance. The case of Ente Nazionale Idrocarburi (1956–1965)*. (21st December 2016) - ZANIER, VALERIA
Abstract: This article explores the relationship between Chinese officials and Western European industrialists, revealing that in the second half of the 1950s, there already was a specific Western European interest in China's market potential, and that this was met with favour on the Chinese side. In order to become a strong and independent country, the People's Republic of China was especially interested in evaluating a wide range of offers in the chemical and energy sectors. By looking at the early achievements of the Italian company, National Hydrocarbon Holding (Ente Nazionale Idrocarburi, ENI), this article will show how its offer in terms of technology and engineering met with the favour of the Chinese at the beginning of the 1960s. This was just when the local petroleum industry was moving towards self-reliance, which China ultimately achieved, albeit for a short time. Sources show that, despite economic and political constraints, PRC decision-makers were perfectly aware of prices and commercial strategies, as well as of the state-of-the-art technology of the time. Furthermore, China's commercial cooperation with Western European companies in the 1950s–1960s meant that early on Chinese leaders had an opportunity to evaluate market alternatives to their tightly constraining alliance with the Socialist bloc.